Game Edukasi Berbasis Android Sebagai Media Pembelajaran Pengenalan Huruf Dan Angka Untuk Anak Usia Dini - Kadek Tame Jaya; M. Ghufroni An’Ars; Ade Surahman; Sanriomi Sintaro (CV. Keranjang Teknologi Media, 2023)
The problem in this study is that there are many learning media that can be used in the learning process, but not all can understand the learning because basically students still like to play so learning media in the form of educational games are needed which can later be used as learning media. Therefore, the learning media presented in this study is in the form of Android-based educational games that are expected to attract the interest and enthusiasm of students in carrying out learning activities. By using the development method, namely Game Development Life Cycle (GDLC) which consists of 6 development phases, starting from the initialization / concept creation phase, preproduction, production, testing, Beta and release. In the design and implementation process, Figma is used for the design process and for the implementation process using the Android Studio application. The result of this study is an educational game as a learning medium for letter and number recognition for early childhood. With test results that have a percentage of 100% in the Functionality aspect and value test results from TK Kartika Jaya 95.33% and TK Miftahul Anwar 95.33% in the Usability aspect, so it can be concluded that students can adapt to the game and students can play the game